Canadian Immigration Policy and Immigrant Economic Outcomes: Why the Differences in Outcomes between Sweden and Canada? - Garnett Picot; Arthur Sweetman (Institute for the Study of Labor (IZA), 2011)
Immigrants to Canada enjoy labour market outcomes that are more favourable than those for their counterparts in Sweden. In an effort to understand these gaps, Canadas immigration policy and outcomes are contrasted to the Swedish immigration experience. The nature of immigration and structural differences involving the domestic labour markets are hypothesized to provide plausible explanations for at least some of the gap. Additionally, there are dynamic issues related to, for instance, the timing of immigrant entry with respect to the business cycle, and changes in the rates of immigration flows, that may have some impact on labour market outcomes and explain some short- to medium-term aspects of the gap in outcomes. On the other hand, common trends are also observed; both unemployment and earnings outcomes among entering immigrants have deteriorated significantly in Canada since the 1980s, as they have in many western countries including Sweden.
Keywords: J61; J68; 330; immigration; cross-country differences; Canada; Sweden; Einwanderung; Migrationspolitik; Arbeitsmarktintegration; Vergleich; Kanada; Schweden